A Truthful Mechanism for Offline Ad Slot Scheduling - Feldman, Jon; Muthukrishnan, S.; Nikolova, Evdokia; Pál, Martin (Algorithmic Game Theory, 2008)
We consider the Offline Ad Slot Scheduling problem, where advertisers must be scheduled to sponsored search slots during a given period of time. Advertisers specify a budget constraint, as well as a maximum cost per click, and may not be assigned to more than one slot for a particular search. We give a truthful mechanism under the utility model where bidders try to maximize their clicks, subject to their personal constraints. In addition, we show that the revenue-maximizing mechanism is not truthful, but has a Nash equilibrium whose outcome is identical to our mechanism. Our mechanism employs a descending-price auction that maintains a solution to a certain machine scheduling problem whose job lengths depend on the price, and hence are variable over the auction.